2005
DOI: 10.1073/pnas.0504407102
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle tracking of murine polyoma virus-like particles on live cells and artificial membranes

Abstract: The lateral mobility of individual murine polyoma virus-like particles (VLPs) bound to live cells and artificial lipid bilayers was studied by single fluorescent particle tracking using total internal reflection fluorescence microscopy. The particle trajectories were analyzed in terms of diffusion rates and modes of motion as described by the moment scaling spectrum. Although VLPs bound to their ganglioside receptor in lipid bilayers exhibited only free diffusion, analysis of trajectories on live 3T6 mouse fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
263
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(274 citation statements)
references
References 40 publications
11
263
0
Order By: Relevance
“…experimental values with diffusion on solid-supported lipid bilayers formed from the fusion of single unilamellar vesicles of these same lipids (8) and found slower diffusion for bilayers, a 2-dimensional diffusion D ϭ 0.01 m 2 ⅐s Ϫ1 , which agrees with literature (9). Although it is true that diffusion on the supported bilayer is expected to be slower than diffusion along the tubes owing to friction from the solid substrate underneath, such reduction is expected to be on the order of a factor of 2, the amount that friction from the supporting substrate reduces diffusion in supported bilayers compared with free-standing giant unilamellar vesicles (10).…”
Section: Resultssupporting
confidence: 80%
“…experimental values with diffusion on solid-supported lipid bilayers formed from the fusion of single unilamellar vesicles of these same lipids (8) and found slower diffusion for bilayers, a 2-dimensional diffusion D ϭ 0.01 m 2 ⅐s Ϫ1 , which agrees with literature (9). Although it is true that diffusion on the supported bilayer is expected to be slower than diffusion along the tubes owing to friction from the solid substrate underneath, such reduction is expected to be on the order of a factor of 2, the amount that friction from the supporting substrate reduces diffusion in supported bilayers compared with free-standing giant unilamellar vesicles (10).…”
Section: Resultssupporting
confidence: 80%
“…With this technique, the individual steps of the entry process and the dynamics of these processes can be elucidated. SVT has been utilized to investigate the entry and trafficking of several viruses including adeno-associated virus (Bräuchle et al 2002;Seisenberger et al 2001), adenovirus (Suomalainen et al 1999), simian virus 40 (Damm et al 2005), murine polyoma virus (Ewers et al 2005), HIV (McDonald et al 2002), influenza virus (Lakadamyali et al 2003;Rust et al 2004), rabies virus (Finke et al 2004) and murine leukemia virus (Lehmann et al 2005). From the trajectories of individual viruses, the interactions between these particles and different cellular components can be directly observed.…”
Section: Introductionmentioning
confidence: 99%
“…In supported membrane bilayers, the viruses are highly mobile, no confinement is observed (Ewers et al 2005;Kukura et al 2009). However, an exception can be observed when the bilayer contains high amounts of GM1 (1 mol %).…”
Section: Association Of Gsls and Ligands With Lipid Domainsmentioning
confidence: 99%
“…Single particle tracking has shown that when incoming mPy viruses bind to the PM of cells, they first undergo random lateral movement for 5 -15 sec with a diffusion constant of 0.01 mm 2 /sec (Ewers et al 2005). The permanent or transient loss of mobility after the initial phase of free diffusion depends on the actin cytoskeleton.…”
Section: Association Of Gsls and Ligands With Lipid Domainsmentioning
confidence: 99%